Green synthesis of noble metal nanoparticles using cysteine-modified silk fibroin: catalysis and antibacterial activity - Das, Soumen; Dhar, Basab Bijayi (RSC Advances, 2014)
Noble metal nanoparticles (NPs) have shown remarkable potential for numerous applications. In this work, a simple, one-pot, green method for the synthesis of gold, silver, palladium, and platinum NPs by using thiol-modified silk fibroin (SF-SH) has been described. The incorporation of thiol groups into silk fibroin (SF) yields small, mono-dispersed metal nanoparticles with good colloidal stability. UV-Vis, transmission electron microscopy (TEM), and X-ray powder diffraction (XRD) analyses show the formation of NPs, and thermo-gravimetric analysis (TGA) data reveal interaction of the NPs with thiol-modified SF. We also show that all the NP-SF conjugates catalyse the reduction of p-nitrophenol to p-aminophenol in the presence of NaBH4 at room temperature. The NP-SF conjugate materials were processed into different material formats like porous scaffolds and films without compromising their individual properties. The Au-SF-SH composite scaffold was used successfully in the heterogeneous catalysis of p-nitrophenol reduction using NaBH4 while the Ag-SF-SH conjugated film showed good antibacterial activity.